2016
DOI: 10.1261/rna.055236.115
|View full text |Cite
|
Sign up to set email alerts
|

The small RNA SraG participates in PNPase homeostasis

Abstract: The rpsO-pnp operon encodes ribosomal protein S15 and polynucleotide phosphorylase, a major 3 ′ -5 ′ exoribonuclease involved in mRNA decay in Escherichia coli. The gene for the SraG small RNA is located between the coding regions of the rpsO and pnp genes, and it is transcribed in the opposite direction relative to the two genes. No function has been assigned to SraG. Multiple levels of post-transcriptional regulation have been demonstrated for the rpsO-pnp operon. Here we show that SraG is a new factor affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…In E. coli , PNPase degrades aberrant pre-tRNAs ( Li et al, 2002 ). We also obtained mutations in sraG , which encodes a small RNA that regulates pnp mRNA levels ( Fontaine et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…In E. coli , PNPase degrades aberrant pre-tRNAs ( Li et al, 2002 ). We also obtained mutations in sraG , which encodes a small RNA that regulates pnp mRNA levels ( Fontaine et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggested that multiple sRNAs in E. piscicida deeply participated in resisting to acid pressure. sRNA040 is homologous with sraG, which was reported to participates in PNPase homeostasis [ 48 ], but there is no report of sraG about acid tolerance to the present. During iron deficiency stress, the expressions of 26 sRNAs changed significantly in E. piscicida , the amount of upregulated sRNAs were basically equal to those of downregulated sRNA among the DEsRNAs expressions.…”
Section: Discussionmentioning
confidence: 99%
“…However, SdsR clearly has regulatory effects rather than simply functioning as a toxin; presumably, RyeA acts to modulate these effects as well (51, 52). Thus far, the only Hfq-independent antisense RNAs regulating something other than a toxin are SraG, encoded antisense to the pnp-rpsO mRNA and reported to downregulate levels of PNPase (53), and the uncharacterized RyjB sRNA, encoded antisense to sgcA.…”
Section: General Srna Categoriesmentioning
confidence: 99%